Mt. Pinatubo: A Case of Mass Extinction of Plant Species in the Philippines - Madulid, Domingo A. (Silliman Journal, 2024)
The eruption of Mt. Pinatubo in Zambales in July 1991 caused serious damage to the vegetation of that mountain and its vicinity. It is feared that several of the more than 60 endemic species recorded in this area have succumbed to the intense heat, ash fall, and lava flow that accompanied the eruption. A detailed floristic inventory of the mountain in the near future will give information on what plants survived and recovered.